2020
DOI: 10.5114/aoms.2020.97847
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low-density lipoprotein cholesterol level calculated using the modified Martin/Hopkins estimation or the Friedewald formula with direct homogeneous assay measured low-density lipoprotein cholesterol

Abstract: Introduction: Low-density lipoprotein cholesterol (LDL-C) represents the primary lipoprotein target for reducing cardiovascular risk (CV). The aim of our study is to compare the direct and the calculated LDL-C levels in the range below 1.8 mmol/l and 2.6 mmol/l depending on triglycerides, and to evaluate the variation in remnant lipoprotein cholesterol. Material and methods: We investigated 14 906 lipid profiles from fasting blood samples of Hungarian individuals with triglycerides < 4.5 mmol/l. Total choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Nakoniec, Martin-Hopkins rovnica je menovite doporučovaná už aj v niektorých národných klinických guidelinoch, postupne odvodzovaných od uvedených dvoch európskych guidelinov, napr. v poľskom (4), a podporu jej vyslovujú aj maďarskí autori (5).…”
Section: úVodunclassified
“…Nakoniec, Martin-Hopkins rovnica je menovite doporučovaná už aj v niektorých národných klinických guidelinoch, postupne odvodzovaných od uvedených dvoch európskych guidelinov, napr. v poľskom (4), a podporu jej vyslovujú aj maďarskí autori (5).…”
Section: úVodunclassified
“…It is agreed that accurate measurement of LDL-C is pivotal in ensuring correct assessment of patients’ cardiovascular risk and treatment of dyslipidemia, targeted at lowering their LDL concentration [ 25 ]. In 2021, ESC the published guidelines recommending that patients be first categorized according to the Systemic Coronary Risk Estimation 2 (SCORE2) and Systemic Coronary Risk Estimation 2-Older Persons (SCORE2-OP).…”
Section: Discussionmentioning
confidence: 99%
“…A good deal of external validations confirm that Martin/Hopkins equation outperforms others in accuracy. 11 24 26 27 28 29 30 31 32 33 34 35 36 …”
Section: Methodsmentioning
confidence: 99%
“…Many external validation studies have been conducted and showed superiority of the Martin/Hopkins 11 24 26 27 28 29 30 31 32 33 34 35 36 or NIH Equation 2 25 27 37 38 in relation to the Friedewald formula. Here, the purpose of this study was to assess the practical differences 39 40 in LDL-C estimates calculated by Friedewald, Martin/Hopkins, or NIH equation 2 in a population-based, random-sampled, noninstitutionalized general U.S. sample.…”
Section: Introductionmentioning
confidence: 99%